PbMYB5 transcription factor plays a role in regulating anthocyanin biosynthesis in pear (Pyrus bretschneideri Rehd) skin - Li, Shangyun; Yang, Yutao; Zhou, Zhiwei; Zhou, Xuan; Lei, Diya; He, Ruiyuan; Zhang, Yunting; Zhang, Jiliang; Lin, Yuanxiu; Wang, Yan; Li, Mengyao; He, Wen; et al. (Frontiers in Plant Science, 2025)
The phenylacetone pathway, which encompasses flavonoids, lignin, and other compounds, is of paramount importance in determining the quality of pear fruit. Nevertheless, the precise regulatory functions of R2R3-MYB transcription factors in the metabolic pathways that regulate pear color changes remain unclear. In this study, we isolated an R2R3-PbMYB5(PbMYB5) transcription factor from ‘Red Zaosu’ pears and demonstrated that it influenced the expression of several genes, including PbCAD1, PbF5H, PbLAR, PbANR, and PbUFGT. The overexpression of PbMYB5 resulted in a notable elevation in anthocyanin concentration within the pear epidermis. Further research has shown that PbMYB5 is able to bind to PbANS and also has interactions with PbbHLH3 and PbbHLH33.We proposed that PbMYB5 forms a complex with PbbHLH3, PbbHLH33, and PbWD40 to activate PbANS and promote anthocyanin accumulation. This study offers new insights into the regulation of various metabolic pathways that impact fruit coloration.